Involvement of glutamate and reactive oxygen species in methylmercury neurotoxicity - Aschner,M. (2007)
This review addresses the mechanisms of methylmercury (MeHg)-induced neurotoxicity, specifically examining the role of oxidative stress in mediating neuronal damage. A number of critical findings point to a central role for astrocytes in mediating MeHg-induced neurotoxicity as evidenced by the following observations: a) MeHg preferentially accumulates in astrocytes; b) MeHg specifically inhibits glutamate uptake in astrocytes; c) neuronal dysfunction is secondary to disturbances in astrocytes. The generation of reactive oxygen species (ROS) by MeHg has been observed in various experimental paradigms. For example, MeHg enhances ROS formation both in vivo (rodent cerebellum) and in vitro (isolated rat brain synaptosomes), as well as in neuronal and mixed reaggregating cell cultures. Antioxidants, including selenocompounds, can rescue astrocytes from MeHg-induced cytotoxicity by reducing ROS formation. We emphasize that oxidative stress plays a significant role in mediating MeHg-induced neurotoxic damage with active involvement of the mitochondria in this process. Furthermore, we provide a mechanistic overview on oxidative stress induced by MeHg that is triggered by a series of molecular events such as activation of various kinases, stress proteins and other immediate early genes culminating in cell damage.